SOCIOECONOMIC FACTORS AND ACCESS TO NUTRITION INFORMATION ASSOCIATED WITH STUNTING AMONG CHILDREN UNDER TWO YEARS IN MALANG CITY - Nadia Farah Diba; Alfi Rahmatillah Nur Fithriah (PRIMA WIYATA HEALTH, 2026)
Background: Stunting remains a major chronic nutritional problem in developing countries, including Indonesia. It results from long-term nutritional deficiency during the first one thousand days of life, leading to impaired physical growth and cognitive development. Socio-economic factors and access to nutrition information are key determinants association child nutritional status. Objectives: To analyze the influence of socio-economic factors and access to nutrition information on the prevalence of stunting among children under two years old in Malang City. Methods: An observational analytic study with a case-control design was conducted from June to July 2025 in Malang City. A total 152 respondents (76 stunted cases and 76 non-stunted controls), selected through multistage random sampling across five randomly selected primary health centers representing five districts in Malang City. Data were collected using a self-developed, expert-validated, and reliable questionnaire (Cronbach’s Alpha=0.718). Data were analyzed using SPSS Statistics software version 22. The chi-square test was applied to determine associations, with a 95% confidence interval and a significance level of α=0,05, and multivariate analysis was performed using multiple logistic regression.  Results: Bivariate analysis showed that maternal education p=0.008 (OR=2.485; 95%CI: 1,266–4,878), family income p=0.001 (OR=3.198 95%CI; 1,633–6,262), family size p=0.000 (OR=3.563; 95%CI: 1,815–6,993), and nutrition information exposure p=0.015 (OR=2.242; 95%CI: 1,168–4,303) were all significantly associated with stunting. However, after adjustment in the multivariate model, only family size remained an independent, significant determinant (aOR=3.03; 95% CI: 1.491–6.166; p=0.002); toddlers from households with more than four members had approximately three times higher risk of stunting compared to those from smaller households. The model explained 18.2% of the variance in stunting occurrence (Nagelkerke R²=0.182), with an overall classification accuracy of 72.4%. Conclusion: Family size was the most dominant and independent determinant of stunting among toddlers in Malang City, while maternal education, family income, and nutrition information access appeared to operate indirectly through this structural pathway. These findings suggest that stunting reduction strategies in urban settings such as Malang City should move beyond nutrition education alone and integrate family planning and per-capita income-based social protection programs into multisectoral stunting convergence efforts.